Target recycling product-bridged DNAzyme walker for sensitive detection of microRNA - Ning Pan; Xiangao Jiang; Weixia Qiu; Xiaxia Qiu; Xinchun Ye; Saiduo Liu (Journal of Analytical Science and Technology)
Abstract The precise and sensitive detection of miRNA is significant for assessing infectious illnesses, particularly pneumonia. However, constrained by the low abundance of miRNA in samples, the majority of miRNA detection approaches employing a one-to-one signal-triggered approach (where one target elicits one signal) proved impractical. We present a target-mediated DNAzyme bridge-induced DNA walker system, characterized by a one-to-more signal-triggered model that amplifies the detection signal and improves sensitivity. The s1/s2@AuNPs are formed by integrating multiple s1 chains and numerous FAM-labeled substrate strands (s2) onto a single gold nanoparticles (AuNPs), creating three-dimensional DNA tracks. The construction of the target recycling induces a connection between the DNAzyme unit and the s1 chain, enabling the assembly of the DNAzyme-induced DNA walker. The DNAzyme motor operated autonomously, with each step driven by DNAzyme-catalyzed substrate cleavage and the cleavage of a fluorescent molecule, facilitating progressive movement along AuNPs-based tracks and an increase in fluorescence. The DNAzyme motor demonstrated exceptional sensitivity and notable selectivity for miRNA, offering possibilities for the assessment of infectious disease.